Canaanite Votive Offerings and Their Significance within Their Context at Tel Burna - Eshed, Vered (Israel exploration journal, 2021)
Excavation at the Chalcolithic site of Fazael 2 in the Jordan Valley in 2013 revealed a third infant burial, in addition to the two previous burials excavated at the site in 2006. This burial, uncovered at the northwestern corner of a rectangular structure in the courtyard of the complex, was primary, found in articulation on a sherd below the floor, and was covered by another large sherd. Infant burials with the body placed on a sherd and covered by another sherd are known from other sites dated from the Pottery Neolithic/Early Chalcolithic period to the Early Bronze Age I. This burial practice is discussed below in relation to other infant and fetus burial practices during this timespan in the southern Levant